PENGUKURAN OVERALL EQUIPMENT EFFECTIVENESS (OEE) DENGAN LABVIEW 8.5 SEBAGAI PENGENDALI MAINTENANCE - Syafrizal Syarief (Politeknik Negeri Jakarta, 2015)
Abstract Total Productive Maintenance (TPM) is a philosophy that aims to maximize the effectiveness of the facilities used in industry, it is applied to analyze problems that occur on any equipment and machinery with a method of calculation of Overall Equipment Effectiveness (OEE) of product quality. Value is determined by OEE Availability, Performance and Yield / Quality. LabVIEW (Laboratory Virtual Instrument Engineering Workbench) software is dedicated to the activities of the interface and control electronic devices by using a personal computer (PC). LabVIEW program allows to operate the instrument, measure and analyze data accurately, and show results quickly. PT OEI which produces DC Fan Motor for computers wants to know the value of OEE of production machinery as a basis for maintenance policy. The 4 types of machines studied have value of 94% Availability, Performance 54.055%, 99.24% and OEE Quality 50.416%. According to Nakajima performance is very low (standard> 90%) and resulted in OEE low, this is the effect of the low speed machines. The measurement is done with the method xl windows and LabVIEW 8.5, while measurements with LabVIEW 8.5 is much more practical and can display OEE variables simultaneously with attractive appearance that will facilitate the maintenance control. Keywords: TPM, OEE, LabVIEW 8.5.